If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2(x + 5) = 8 + -5 Reorder the terms: 3x + -2(5 + x) = 8 + -5 3x + (5 * -2 + x * -2) = 8 + -5 3x + (-10 + -2x) = 8 + -5 Reorder the terms: -10 + 3x + -2x = 8 + -5 Combine like terms: 3x + -2x = 1x -10 + 1x = 8 + -5 Combine like terms: 8 + -5 = 3 -10 + 1x = 3 Solving -10 + 1x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 1x = 3 + 10 Combine like terms: -10 + 10 = 0 0 + 1x = 3 + 10 1x = 3 + 10 Combine like terms: 3 + 10 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| 18x=-32 | | A=2b+20 | | 8+3x-9=4x-9 | | 18+7x-7=4x+17 | | 8x-6+x+8=20 | | -5y-(-6-2y)=0 | | 2x+16+15=11x-5 | | 7x+x+19=10x+3 | | a+3=7-a | | X+12+14=3x | | 2x+14=3x-5 | | 24x=23x+15 | | 38x=39x-19 | | 6x+11=5x+17 | | 10q-5p= | | 7x+4-= | | 2x=35-x^2 | | 3-x=5+2 | | 1.89L-6L= | | 32/3-71/2= | | X^2+x^4=12 | | 15.75-32.5= | | 5g+3(-8+5g)=1-g | | 6-x+5= | | 37.5=5+n | | f-3/4=11/2 | | 5/6=43/5 | | 2x^2+12xy+7y^2=-1 | | 4x^2+148x-680=0 | | 4(2x-5)+8=26 | | 5x+60=7+5x | | 9(11-a)=3(3a-9) |